Collisionless losses of fast ions in the divertor tokamak test due to toroidal field ripple. (27th September 2021) - Spizzo, G.; Gobbin, M.; Agostinetti, P.; Albanese, R.; Ambrosino, R.; Casiraghi, I.; Cecconello, M.; Falessi, M.V.; Granucci, G.; Mantica, P.; Martin, P.; Vallar, M.; et al.
Abstract: In this paper we analyze fast ion motion in the divertor tokamak test (DTT) device (Albanese et al 2017 Nucl. Fusion 57 016010). It is planned that DTT will be heated through a mix of 45 MW heating power, including 15 MW negative-ion-based neutral beam heating (NNBI) which is currently being developed by Consorzio RFX in Padova, Italy (Agostinetti et al 2019 Fusion Eng. Design 146 441–446). An issue for DTT is that a toroidal field (TF) ripple with a maximum value of about ∼0.42% (with respect to the on-axis magnetic field B 0 ) is expected on the low-field side, and this ripple interacts with fast ions through the rather well-known phenomena of ripple-precession resonances, in addition to prompt losses of ions which do not complete a full orbit in the poloidal plane. We will show that, with the planned geometry of NNBI, prompt losses are negligible, and ripple-precession losses amount to a maximum of 0.15%. The calculations are performed with the guiding center code Orbit using two different equilibria, and a beam with an energy of 400 keV and the injection angle α inj = 40° (measured w.r.t. the first wall), which corresponds to a pitch of injected particles λ = v ∥ / v ≈ sin α inj = 0.65. The main resonances are of the form ω b − nNω d = 0, ω b and ω d being the bounce and precession frequency, respectively, N = 18 the ripple periodicity and 3 ⩽ n ⩽ 6 are the toroidal wavenumbers of the resonances. Although collisionless interaction with the TF ripple does not pose a serious threat to the NNBI project, an open question remains as to whether the presence of these resonances will interact with fast particles accelerated by Alfvén eigenmodes, and if stochastization of the resonances is possible in DTT, as was observed in the past in TORE SUPRA.